THU0474 Utilisation of anti-osteoporotic drugs in real-world data: an analysis of persistence to therapy and risk of fracture. (12th June 2018) - Orlando, V.; Monetti, V.M.; Guerriero, F.; Moretti, A.; Russo, V.; Piscitelli, A.; Iolascon, G.; Menditto, E.
Abstract : Background: Osteoporosis is a chronic progressive disease characterised by low bone mass and deterioration of bone structure, leading to an increate risk of fractures. It is a major public health problem, affecting hundreds of millions of people worldwide. The primary aim of pharmaceutical therapy is to reduce the risk of osteoporotic fractures. However, long-term adherence to therapy is requie for optimal therapeutic benefit for patients with osteoporosis. Poor adherence is considered to be one primary reason for suboptimal clinical benefit. Objectives: The aim of this study was to investigate the determinants of non-persistence and impact of persistence on the risk of fractures by using administrative databases. Methods: We conducted a retrospective cohort study using administrative data from four local health authorities in the Abruzzo Region (Central Italy), which comprise about 9 00 000 inhabitants (68% of the overall regional population). The final cohort consisted of a total of 7862 patients, aged ≥60 years, identified through records of filled prescriptions for an antiosteoporotic drug between January 1, 2006 to December 31, 2006. The primary outcome of this study was persistence at one year. Persistence was defined as the length of time (in days) from the date of the index prescription to the date of discontinuation therapy. Results: Kaplan – Meier analysis showed that 3733 patients (47.5%) were persistent with antiosteoporotic drugs after 1 year. An adjusted analysis showed that there is a big difference in persistence between women and men: women are more likely to be non-persistent than men (HR:1.94). Switcher patients were more likely to be non-persistent (HR:1.22). The odds of fracture were significantly higher for patients with previous fractures in comparison with those without previous fractures [OR, 1.70, (95% CI, 1.12–2.59)] (table 1) Table 1 Logistic regression model: impact of persistence and other factors on the risk fracture Conclusions: Persistence with antiosteoporotic drugs is a significant predictor of incurring a fracture. For these reason, improving osteoporosis treatment compliance and persistence represents one of a major challenge for the future. References: [1] Casula M, Filippi A, Flacco E, Gambera M, Manzoli L, Menditto E, Orlando V, Piccinelli R, Tragni E, Catapano A. Assessment and potential determinats of compliance and persistence to anti-osteoporosis therapy in Italy. Am J Manag Care2014;20(5):e138-e145. [2] Iolascon G, Gimigliano F, Orlando V, Capaldo A, Di Somma C, Menditto E. Osteoporosis drugs in real-world clinical practice: an analysis of persistence. Aging Clin Exp Res2013Oct;25 Suppl 1:S137–41. Disclosure of Interest: None declared